Experimental Verification of the Influence of Inner and Outer Groove Radius of High-speed Bearings on Operating Temperature Rise - Haibo Lin; Jianxi Yang (Jixie chuandong)
The characteristics of temperature rise of deep groove ball bearing under working condition are studied. By analyzing the influence of groove curvature radius，degree of closure and other parameters on the heat generation of the ball bearing，the size parameters such as inner ring groove radius （inner groove curvature radius） and outer ring groove radius （outer groove curvature radius） are optimized through the modification design of the bearing structure. The relationship between the curvature radius coefficient of inner and outer groove and the working temperature of bearing under different bearing pressure and rotating speed are obtained by experimental method. The results show that the curvature coefficient of the inner and outer ring channel has a great influence on the temperature rise of the bearing. The study provides a reference for optimizing the contact matching between the inner and outer grooves of the bearing and the steel ball，enabling a better lubrication of the bearing working surfaces，further improving its heat dissipation conditions，reducing sliding friction to reduce the friction torque and noise of the bearing，so as to realize the high speed，high efficiency，low power consumption and low noise of the bearing. The research results have guiding significance for parameter optimization of high speed deep groove ball bearing.